PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN NARKOBA - Krismiyarsi S.H., M.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
Narcotics and psychotropic actually only use for the treatment and the development of science, however, lately often misused is not used as intended. Law enforcement again t drug abuse by law enforcement officers are police officers as the spearhead of the criminal justice system, attorney, and court. Law enforcement against drug abuse is done by a variety of efforts such as : pre emtif efforts, preventive efforts, the efforts made by check urine and rasia-rasia, and efforts refresif. That is done the againts drug abuse experiencing barriers are :lack of budget from the Government to conduct operations in the control and prevention of drug abuse, lact of infrastructure, the limited number of vehicles that can be used for operational, weak human resources owned by Police, both in terms of number, of psychic ability, lack of coordination and integration between the agencies involved in drug law enforcement process. As well as criminal chargers and the verdict is too light.